Lived Experiences of Filipino Nurses Working in the Medical and Surgical Departments of Darlington Memorial Hospital, United Kingdom - Jezalyn O. Vargas; Jane M. Tagum-Briones; Cyril B. Romero; Carlen Lagyap De Villa (Buletin Ilmu Kebidanan dan Keperawatan, 2026)
This study explored the lived experiences of twenty-six (26) Filipino nurses working in the medical and surgical departments of Darlington Memorial Hospital (DMH), United Kingdom. Using a descriptive research design and a self-developed, expert-validated survey, the study examined their cultural adaptation, workplace environment, and support systems. It also analyzed the relationship between their demographic profiles (age, sex, civil status, length of service, and department) and these experiences. The results showed that most respondents were young (31–40 years old), female, married, and relatively new to DMH (1–3 years of service), with many working in the Operating Room. Overall, participants expressed positive experiences (grand mean = 3.16), with the workplace environment receiving the highest rating (mean = 3.29, "Strongly Agree"), particularly in understanding local healthcare practices. Cultural adaptation received the lowest rating (mean = 3.08, "Agree"), with participation in local community events identified as the most challenging aspect. Statistical analysis revealed significant relationships between age and all aspects of lived experience, between civil status and both cultural adaptation and support systems, and between length of service and both cultural adaptation and workplace environment. No significant association was found between department type and the nurses’ lived experiences. Based on these findings, the study recommends implementing culturally sensitive training, language and technical skills development, mentorship programs, enhanced mental health support, and community engagement initiatives. It also encourages experienced Filipino nurses to mentor newcomers and suggests that relevant Philippine agencies support these professionals through housing assistance and active workplace engagement.